2022
DOI: 10.24198/obgynia/v5n1.345
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Luaran Maternal dan Perinatal Terhadap Tingkat Keparahan Infeksi COVID-19

Abstract: Tujuan: Penelitian ini dilakukan untuk mengetahui hubungan luaran maternal dan perinatal terhadap tingkat keparahan infeksi COVID-19 pada ibu bersalin di RSUP Dr. Hasan Sadikin Bandung. Metode: Penelitian ini menggunakan studi analitik observasional retrospektif dengan rancangan potong lintang menggunakan data rekam medik selama periode Maret 2020 hingga Juni 2021. Karakteristik subjek meliputi usia ibu, jumlah paritas, tingkat pendidikan, dan usia kehamilan. Luaran maternal meliputi hipertensi pada kehamilan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The placenta is a site for circulation of blood and oxygen for the fetus, so when there is no damage to the placenta, the flow of oxygen to the fetus will remain smooth so that the baby can be born with a good APGAR score. 24 The study finding is in line with the study conducted at the Ulin Regional General Hospital in Banjarmasin which found that there was no difference in the outcome between infants born to preeclampsia women with Covid-19 and infants born to preeclampsia women who not have Covid-19.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The placenta is a site for circulation of blood and oxygen for the fetus, so when there is no damage to the placenta, the flow of oxygen to the fetus will remain smooth so that the baby can be born with a good APGAR score. 24 The study finding is in line with the study conducted at the Ulin Regional General Hospital in Banjarmasin which found that there was no difference in the outcome between infants born to preeclampsia women with Covid-19 and infants born to preeclampsia women who not have Covid-19.…”
Section: Discussionsupporting
confidence: 87%
“…A study conducted at RSUP Dr. Hasan Sadikin Central General Hospital of Bandung found that asphyxia among newborns had a significant relationship with the severity of Covid-19. 24,25 Delivery factors make a major contribution to the incidence of neonatal asphyxia. Since the factors of delivery especially prolonged labor is included in the high risk, it is very likely that baby born will experience neonatal asphyxia.…”
Section: Discussionmentioning
confidence: 99%